Physiology mechanisms of exercise for PTSD: a narrative review - Dong, Hongding; Lin, Zhiyi (Frontiers in Psychology, 2025)
In at-risk societies, the population of post-traumatic stress disorder (PTSD) incidence is gradually expanding from veterans to the general public. In the face of the high incidence of PTSD, exercise therapy, as an economical and maneuverable treatment, has not received the attention it deserves. In this paper, the literature on PTSD symptom improvement through comb-climbing exercise interventions found that performing long-term exercise can achieve significant improvement in PTSD symptoms by modulating the central nervous system, autonomic nervous system, and immune system at the physiological level. Aerobic exercise (running, walking) is beneficial to the central nervous system and immune system; anaerobic exercise positively affects the autonomic nervous system, including resistance or strength endurance training; yoga, which focuses on flexibility and balance training, has a positive effect on the immune system. Future research should explore the neutral and negative effects and mechanisms of exercise on PTSD interventions. Expand more empirical studies in special occupational populations. And implement longitudinal intervention studies with PTSD patients to gain an in-depth understanding of PTSD intervention effects.